Effect of polyoxyethylene sorbitan monooleate (Tween 80) on exopolysaccharide and biomass composition of psychrophilic yeast - Rusinova-Videva, Snezhana; Petkova, Zhana; Antova, Ginka; Stoyanov, Plamen; Mladenova, Tsvetelina; Radoukova, Tzenka (Polish Polar Research, 2023)
Studies on the surface-active agents added during the cultivation process proved their effect on the synthesized bioproducts. The biosynthesis and accumulation of exopolysaccharide and biomass by Antarctic producer Cryptococcus laurentii AL65 were studied in submerged cultivation using different carbon sources in the culture medium added to a one-percent concentration (pentoses, hexoses and oligosaccharides). Sucrose was chosen as the most appropriate carbon source for the cell growth and extracellular polymer biosynthesis. Absorption of sucrose by a strain producer was monitored and the residual sugars were traced in the dynamics of the fermentation process. The effect of polyoxyethylene sorbitan monooleate (Tween 80) on the cell growth and the accumulation of the synthesized biopolymer were studied for the first time with the Antarctic producer. The optimal increase in the amount of accumulated exopolysaccharide was recorded at a concentration of 6% Tween 80 at 24 h from the start of fermentation. The surfactant treatment contributed to an increase in the total amount of lipids in the cell, to the increased biosynthesis of unsaturated fatty acids compared to saturated ones, and to the increased cellular synthesis of valuable metabolites such as phosphatidylinositol, phosphatidylserine and phosphatidylethanolamine. The impact of Tween 80 on intracellular and extracellular metabolites is a valuable asset in a possible scale-up of the process in industrial settings.